Increased prevalence of colorectal neoplasia in patients with intraductal papillary mucinous neoplasms. (June 2022) - Zelnik Yovel, Dana; Bear, Lior; Scapa, Erez; Shnell, Mati; Bar Yishay, Iddo; Bar, Nir; ZIv Baran, Tomer; Younis, Fadi; Phillips, Adam; Lubezky, Nir; Shibolet, Oren; Ben-Ami Shor, Dana
Background: The association between intraductal papillary mucinous neoplasms (IPMNs) and colorectal cancer (CRC) and polyps is controversial. Objectives: To compare the prevalence of CRC and colorectal polyps among patients with IPMN and matched average risk individuals. Methods: A match cross-sectional historical study comparing colonoscopy findings of 310 patients with IPMN cysts who underwent at least one colonoscopy examination from 2004 through 2019, with 310 age- and gender-matched average risk participants who underwent a screening colonoscopy. CRC and polyps were assessed in both groups. The prevalence and odds ratio were calculated. Results: CRC was diagnosed in 16 of 310 patients with IPMN (5.2%), and at least one polyp was detected in 96 patients (31%). The prevalence of CRC was greater among patients with IPMN than in matched individuals [5.2% versus 1.3%, p = 0.012, prevalence odds ratio (POR) 4, confidence interval (CI) 1.29–16.44]. The overall prevalence of polyps was not higher among patients with IPMN than in matched individuals (31% versus 26.8%, p = 0.291, POR 1.22, CI 0.85–1.76). However, the prevalence of colorectal adenomas with high-grade dysplasia was higher in patients with IPMN than in matched individuals (4.2% versus 1%, p = 0.02, POR 4.33, CI, 1.19–23.7). The prevalence of large polyps (i.e. more than 20 mm in size) was also greater in patients with IPMN than in matched individuals (6.1% versus 1.9%, p = 0.011, POR 3.6, CI, 1.29–12.40). Conclusion: Patients with IPMN have a significantly higher prevalence of CRC and advanced polyps than the average risk population. In view of our findings, we suggest that once the diagnosis of IPMN is made, special consideration of CRC should be undertaken.